Neural signatures of co‐occurring reading and mathematical difficulties. Issue 6 (19th June 2018) - Skeide, Michael A.; Evans, Tanya M.; Mei, Edward Z.; Abrams, Daniel A.; Menon, Vinod
Abstract: Impaired abilities in multiple domains is common in children with learning difficulties. Co‐occurrence of low reading and mathematical abilities (LRLM) appears in almost every second child with learning difficulties. However, little is known regarding the neural bases of this combination. Leveraging a unique and tightly controlled sample including children with LRLM, isolated low reading ability (LR), and isolated low mathematical ability (LM), we uncover a distinct neural signature in children with co‐occurring low reading and mathematical abilities differentiable from LR and LM. Specifically, we show that LRLM is neuroanatomically distinct from both LR and LM based on reduced cortical folding of the right parahippocampal gyrus, a medial temporal lobe region implicated in visual associative learning. LRLM children were further distinguished from LR and LM by patterns of intrinsic functional connectivity between parahippocampal gyrus and brain circuitry underlying reading and numerical quantity processing. Our results critically inform cognitive and neural models of LRLM by implicating aberrations in both domain‐specific and domain‐general brain regions involved in reading and mathematics. More generally, our results provide the first evidence for distinct multimodal neural signatures associated with LRLM, and suggest that this population displays an independent phenotype of learning difficulty that cannot be explained simply as a combination of isolated low reading and mathematical abilities. Abstract : BLURB: Children with co‐occuring learning deficits in the domains of reading and mathematics reveal an independent phenotype of neurodevelopmental aberrations to both domain‐general and domain‐specific systems that distinguishes them from children with isolated deficits in a single domain.